Transforming Education: The Impact of Cloud Computing on Data Management and Student Learning - Rinovian R Rinovian R; Suroso Suroso (Journal Basic Science and Technology, 2024)
This research examines the utilization of cloud computing technology in education and its implications for teaching, learning, and administrative practices within educational institutions. Through a synthesis of existing studies, the research identifies key findings, trends, and recommendations that shape the landscape of educational cloud computing. The findings highlight the transformative potential of cloud computing in enhancing accessibility, collaboration, efficiency, and innovation in education. Educators, administrators, policymakers, and students play crucial roles in leveraging cloud-based tools and platforms to personalize learning, streamline administrative processes, and promote digital equity. Looking to the future, emerging trends such as artificial intelligence (AI), augmented reality (AR), virtual reality (VR), blockchain, and edge computing are poised to revolutionize educational practices. Prioritizing cybersecurity, data privacy, and strategic planning will remain essential as educational institutions increasingly rely on cloud computing for data management and instructional delivery.